Distillers feeds from various grains as protein sources for pigs - Näsi, Matti (Agricultural and Food Science, 1985)
The nutrient digestibility and protein utilization of distillery feeds derived from dehulled barley, rye and wheat were studied with growing pigs receiving one of eleven diets in which the protein sources were BDDGS, RDDGS, WDDGS, BDDG, BDS or SBM. In a second trial BDDGS and BDDG were compared with the same feeds treated prior to cooking with cellulase enzyme. The diets, consisting of barley and distillers feed, were fortified with L-lysine and DL-methionine to achieve levels of 13.0 % DCP, 0.80 % lysine and 0.56 % S amino acids. The distillery by-products contained crude protein 24.8—41.5 %, crude fat 6.3—9.5 %, crude fibre 7.1 10.3 %, ADF 18.2—22.9%, NDF 33.3—43.7 % and ADL 8.7—11.3 % on a dry basis. Their lysine content was 0.43—1.36 % of DM and their S amino acid content 0.58—1.36 %. The digestibilities of organic matter and crude protein were 56—83 and 56—79 %. DDGS from rye had low digestibilities and barley distillers solubles high. The cellulase treatment decreased the OM and CP digestibilities by 6.4—10.4 and 15.3—15.4 % units, respectively. FU/kg DM varied from 0.63 to 0.84 and DCP from 177 to 405 g/FU. The N retention of the BDDGS, RDDGS, WDDGS, BDDG, BDS and SBM diets was, respectively, 21.7, 21.1, 24.2, 23.0, 17.7 and 24.6 g/d (P < 0.01) and the biological values were 55, 60, 59, 56, 55 and 66. The daily gains varied from 700 to 762 g. The data indicated that distillery by-products could replace soybean meal quite satisfactorily as a protein source in amino acid-fortified diets.